MAKNA RITUS AHAR DENGAN SAKRAMEN PEMBAPTISAN GEREJA KATOLIK DI KECAMATAN ATADEI KABUPATEN LEMBATA - Homi, Anastasia Priana; Tamelab, Petrus; Kase, Emanuel B.S. (STIPAS Keuskupan Agung Kupang, 2021)
The reason i took this title is because based on my obsevation that there are a large part of the Watuwawer village community who still don’t understand the meaning of the rite Ahar, where they only run and follow this ceremony but lack understanding of the meaning contained in the Ahar ceremmony. Based on the topic of the problem, the author takes a number of theories that are considered important so they can be used as reference material to answer problems in the field and also as material so that the community of Watuwawer can know and understand the meaning contained in the rite of Ahar. For any effort is made to provide understanding to the the public relationship between rite of the Ahar and the sacrament of baptism.The research method used is descriptive method is a method in examining the status of human groups The researech method used is descriptive method with a method in examining the status of human groups, an object, a condition, a system of thought or a class of events in the present and qualitative research is a study used to investigate, dicover, describe and explain the quqlity or privilege of social influences that cannot be explained, masured, or drawn throug a quantitative approach. The results of research in thesis writing said that the rite of Ahar ceremmony with the sacrament of baptism has the same meaning identity to someone. Where a person is baptized or bathed with water wich becomes a symbol that liberates and present a person as a sign of acceptance of someone as a member of the tribe or a member of the church.